Mixing, demixing, and structure formation in a binary dipolar Bose-Einstein condensate - Young-S, Luis E. [UNESP]; Adhikari, Sadhan Kumar [UNESP] (Amer Physical Soc, 2012)
We study the static properties of disk-shaped binary dipolar Bose-Einstein condensates of Er-168-Dy-164 and Cr-52-Dy-164 mixtures under the action of interspecies and intraspecies contact and dipolar interactions and demonstrate the effect of dipolar interaction using the mean-field approach. Throughout this study we use realistic values of interspecis and intraspecies dipolar interactions and the intraspecies scattering lengths and consider the interspecies scattering length as a parameter. The stability of the binary mixture is illustrated through phase plots involving a number of atoms of the species. The binary system always becomes unstable as the number of atoms increases beyond a certain limit. As the interspecies scattering length increases corresponding to more repulsion, an overlapping mixed state of the two species changes to a separated demixed configuration. During the transition from a mixed to a demixed configuration as the interspecies scattering length is increased for parameters near the stability line, the binary condensate shows special transient structures in density in the form of red-blood-cell-like biconcave and Saturn-ring-like shapes, which are direct manifestations of the dipolar interaction. DOI:10.1103/PhysRevA.86.063611